Fuzzy Logic Implementation Using The Tsukamoto Method As A Decision Support System In Scholarship Acceptance - et. al., Sukenda, S.T., M.T, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Scholarships are a supporting factor for students. In the process of determining who receives the scholarship we need a decision-making process is subjective, with the criteria some students who have the ability or value that is not so different. With the existence of a system that supports decision making in determining who is entitled to a scholarship. This system is supported by the Tsukamoto fuzzy logic method which is based on data or human resources rules with criteria that have been determined by a group of people. Therefore, the results of this process will be given to students based on existing decisions.